Upaya MTsS Syekh Ibrahim Harun Tiakar Dalam Mempertahankan Eksistensinya 2000-2021 - Muhammad Nur Fuad; Najmi Najmi (Jurnal Kronologi, 2022)
This research is a historical research on the efforts of Sheikh Ibrahim Harun Tiakar's private Tsawiyah (MTsS) adrasa in maintaining its existence. The purpose of this study is to explain how the background of the emergence of Mtss Syekh Ibrahim Harun Tiakar from Pondok Pesantren to Mtss Syekh Ibrahim Harun Tiakar. And the efforts of Mtss Sheikh Ibrahim Harun in maintaining its existence in 200-2021. The method used in this study is the historical method which consists of heuristics, criticism, interpretation, and historiography. Syekh Ibrahim Harun Tiakar Private Madrasah Tsawiyah (MTsS) Is a madrasa of pride for the Tiakar community during the Dutch period which was formerly called "Surau Bomban" which was founded by Buya Sheikh Ibrahim Harun on March 1, 1929. However, after Buya Sheikh Ibrahim Harun died there was a setback in " Surau Bomban” until it finally stopped completely in 1998. On September 17, 1999, community leaders gathered to revive the Madrasah that was once the pride of the Tiakar community. Over time, the number of enthusiasts at MTsS Sheikh Ibrahim Harun Tiakar has increased rapidly until now. Efforts made by MTsS Sheikh Ibrahim Harun Tiakar in maintaining its existence are, promoting, improving the quality of educators, improving the quality of learning, and channeling students' interests and talents according to students' abilities.